2021
DOI: 10.3390/jof7050368
|View full text |Cite
|
Sign up to set email alerts
|

New Coelomycetous Fungi from Freshwater in Spain

Abstract: Coelomycetous fungi are ubiquitous in soil, sewage, and sea- and freshwater environments. However, freshwater coelomycetous fungi have been very rarely reported in the literature. Knowledge of coelomycetous fungi in freshwater habitats in Spain is poor. The incubation of plant debris, from freshwater in various places in Spain into wet chambers, allowed us to detect and isolate in pure culture several pycnidia-producing fungi. Fungal strains were phenotypically characterized, and a phylogenetic study was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In this study, we extended the spectrum of coelomycetous fungi pathogenic for fish. Although our attempts to find characteristic fruiting bodies in isolated fungus were not successful, phylogenetic analysis clearly identified it as a recently described species of Neopyrenochaeta , N. submersa , described from plant debris in freshwater in Spain [ 12 ]. Problems with induction of sporulation in colelomomycetous fungi are relatively common and make their identification based on phenotype challenging or impossible [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we extended the spectrum of coelomycetous fungi pathogenic for fish. Although our attempts to find characteristic fruiting bodies in isolated fungus were not successful, phylogenetic analysis clearly identified it as a recently described species of Neopyrenochaeta , N. submersa , described from plant debris in freshwater in Spain [ 12 ]. Problems with induction of sporulation in colelomomycetous fungi are relatively common and make their identification based on phenotype challenging or impossible [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 119 samples of plant debris submerged in freshwater in Spain were collected as follows: two in Parque de Doña Casilda Iturriza (Vizcaya province), three in Les Guilleries (Barcelona province), ten in Cúber (Escorca, Mallorca), 22 in Capafonts (Tarragona province), 15 in Pontons (Barcelona province), 17 in Riaza (Segovia province), and 50 in Cascadas del Huéznar (Cazalla de la Sierra, Sevilla province). Samples were placed into sterile self-sealing plastic bags for transport to the laboratory and stored at 5 • C. Samples were processed and examined following the method described previously by Magaña-Dueñas et al [13]. All isolates were stored in the culture collection at the Faculty of Medicine and Health Sciences (FMR), Reus (Spain), and herborized materials and living cultures of novel fungi were deposited in the fungal collection at Westerdijk Fungal Biodiversity Institute (CBS; Utrecht, The Netherlands).…”
Section: Samples Collection and Fungal Isolationmentioning
confidence: 99%
“…DNA extraction, amplification, and sequencing were carried out following the protocols outlined by Magaña-Dueñas et al [13,14]. SeqMan software v. 7.0.0 (DNAStar Lasergene, Madison, WI, USA) was used to obtain and edit the consensus sequences.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…Except for the Ebro, the rivers of the Atlantic slope are the longest [ 13 ]. Spain is a country where the hyphomycetes have been studied for decades, but only in recent years have the sexual states of freshwater ascomycetes and their coelomycetous asexual states begun to be investigated with any great frequency [ 14 , 15 , 16 ]. The present study describes the phenotype and taxonomy of several new species of the Ascomycota found in various freshwater habitats in Spain, all of them isolated from submerged plant debris.…”
Section: Introductionmentioning
confidence: 99%